A Comparison of Search Functionalities in Several Tools Used for Searching within Digital Text Collections. Issue 1 (13th October 2021) - Ball, Liezl H.; Bothma, Theo J.D.
Abstract: The search functionalities that a search tool for a digital text collection offer, will determine how a user can interact with and search in such a collection. This poster considers the search functionalities in four tools that are used to search within digital text collections. Search functionalities that are well known in information science, namely basic word searching, phrase searching, wildcards, Boolean operators, proximity searching, field searching, case sensitive searching, filtering, as well as linguistic search functions will be considered. Knowledge about search functionalities can inform and improve the design of tools for digital text collections.